2019
DOI: 10.1002/ceat.201800574
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Irradiation during the Calcium Sulfate Hemihydrate to Dihydrate Transformation Process

Abstract: The ultrasound-assisted transformation of calcium sulfate hemihydrate (CSH) to calcium sulfate dihydrate (CSD) was studied using three ultrasonic power settings. In addition to continuously measuring the variation in the conductivity value with time, the process was followed by X-ray diffraction and scanning electron microscopy (SEM) analysis. Thermogravimetric analysis, Fourier transform infrared, mass spectrometry, and filtration analyses helped to determine the physicochemical properties of the as-obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Figure 5 shows the thermogravimetric curves of SrCSH and CS-SrCSH. The weight loss of SrCSH is obvious between 100 and 200 • C, which is mainly due to the evaporation of 0.5 mol crystalline water contained in SrCSH at temperatures higher than 100 • C. The weight loss of SrCSH did not decrease once the temperature increased above 300 • C. The final weight loss rate of SrCSH was 90.36%, which is basically consistent with the theoretical value [32]. The CS-SrCSH microspheres exhibit obvious weight loss between 100 • C-200 • C and 300 • C-500 • C, which is mainly due to the gradual carbonization and decomposition of CS film encapsulated on the surface of the microspheres [33,34].…”
Section: Chemical and Structural Characterizationsupporting
confidence: 86%
“…Figure 5 shows the thermogravimetric curves of SrCSH and CS-SrCSH. The weight loss of SrCSH is obvious between 100 and 200 • C, which is mainly due to the evaporation of 0.5 mol crystalline water contained in SrCSH at temperatures higher than 100 • C. The weight loss of SrCSH did not decrease once the temperature increased above 300 • C. The final weight loss rate of SrCSH was 90.36%, which is basically consistent with the theoretical value [32]. The CS-SrCSH microspheres exhibit obvious weight loss between 100 • C-200 • C and 300 • C-500 • C, which is mainly due to the gradual carbonization and decomposition of CS film encapsulated on the surface of the microspheres [33,34].…”
Section: Chemical and Structural Characterizationsupporting
confidence: 86%
“…This is known as a hydration reaction. Some researchers, such as Singh and Middendorf [ 1 ] and Cheng et al [ 3 ], agree that HH hydration leading to DH formation occurs through a dissolution mechanism, i.e., HH particles dissolve in water and then DH precipitates from the aqueous solution by being less soluble than HH [ 4 , 5 , 6 , 7 ]. Using smaller HH particles ensures rapid dissolution before setting begins, which prevents the formation of mesopores [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kondratieva et al 20 found that the adding of SiC accelerates the hydration process of hemihydrate gypsum and increases the length of crystals. Polat and Sayan 21 found that the ultrasound irradiation can shorten the CaSO 7 studied the influence of process parameters on hydration kinetics of hemihydrate phosphogypsum in the simulation of wet process phosphoric acid recrystallization process. Yang et al 22 showed that the exposures of the crystal cylinders of α-HH are positive to hydration reactivity, whereas the exposures of the conical surfaces are negative to hydration reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Kondratieva et al found that the adding of SiC accelerates the hydration process of hemihydrate gypsum and increases the length of crystals. Polat and Sayan found that the ultrasound irradiation can shorten the CaSO 4 ·0.5H 2 O–CaSO 4 ·2H 2 O transformation time and generate more deformed and smaller-sized CaSO 4 ·2H 2 O crystals. Wang et al studied the influence of process parameters on hydration kinetics of hemihydrate phosphogypsum in the simulation of wet process phosphoric acid recrystallization process.…”
Section: Introductionmentioning
confidence: 99%